If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1m = 6(m + 7) Reorder the terms: -1m = 6(7 + m) -1m = (7 * 6 + m * 6) -1m = (42 + 6m) Solving -1m = 42 + 6m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-6m' to each side of the equation. -1m + -6m = 42 + 6m + -6m Combine like terms: -1m + -6m = -7m -7m = 42 + 6m + -6m Combine like terms: 6m + -6m = 0 -7m = 42 + 0 -7m = 42 Divide each side by '-7'. m = -6 Simplifying m = -6
| 3+f=12 | | (7x)=(5x+18) | | 3/4(6)= | | 50=2x-2+x+2x-2+x | | 1.5y=60-4x | | 20=-3(m-4)+11 | | 4x-20=-42 | | 5-6=-11+2x | | -9x-1=18 | | 95y=64x | | 14=-2(m-1)+6 | | y=95x+64 | | 11t+3-8t=40-3t-1 | | 3x^2-18x=48x | | y=3/5 | | y=95+64x | | -4-20+19t=-20t-7(-7-18) | | 3b-12=-6 | | 16.2-3p=57.8 | | v+5.34=5.39 | | -5a-35=5 | | y=95+64 | | -5=5(p+8) | | 10d+2+1-9=94 | | -20w=8w+2(-13w+2) | | 8(2w-1)-4=-116 | | 2*sin(x)+5=6 | | y-7=1.5x-4 | | 2(x+7)=72 | | 4x^2+4x-13=17-15x | | 9.9k-7.4=14.6 | | 4(-3v+1)=20-16v |